THIRD-YEAR HEALTH PROFESSIONS STUDENTS’ INTERPROFESSIONAL EDUCATION IN THE COMMUNITY SETTING: WHAT DID THEY EXPERIENCE? - Siti Rokhmah Projosasmito; Rilani Riskiyana; Supriyati Supriyati (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Learning by experiencing a real situation is believed to be more powerful than using simulation. This hypothesis is also applied to interprofessional learning for students in health professions education. Learning to collaborate and practice students' knowledge of health care in a community became the purpose of the community and family health care (CFHC) program in the Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada.Aim: To describe the third-year students’ experiences of learning interprofessional collaboration in a community setting based on their activity report.Case Discussion: The CFHC team created a particular design for third-year students, focused on community health problems rather than family health problems. The groups conducted focus group discussions to explore health issues and to decide together with the community the main problem that would be given intervention. The groups documented the entire process through a written report, video, and an article about their intervention outcome.Conclusion: The reports showed that students were able to demonstrate interprofessional practice in solving health problems in the community. They learned to work as an interprofessional team while experiencing it. Thus, conducting community-based IPE for undergraduate students is necessary to develop interprofessional collaboration competencies.